Assessing the opinion of hospitalized children aged 5-15 y/o in the Bandarabbas pediatric hospital regarding the color Of the nursing staff's uniforms. - ASHRAF BEIRAMI,; SOMAYEH SOLTANI-NEJAD, (International Journal of Pharma and Bio Sciences, 2018)
The first non-verbal communication between a nurse and pediatric patient is the physical appearance and the color of the nurses clothing uniform which can have a significant effect on the pediatric patient’s mentality. The study is of type descriptive, with regard to the aim of the research; assessment of pediatric patients opinions regarding the nursing uniform color. , The research community includes all patients aged between 5-15 years of age, admitted to the pediatric government hospital under the Ministry and Medical Education of Bandar Abbas. The size of the sample includes 222 pediatric patients and sampling was done un-coincidentally during a 6 month period in the year 1996. To collect the data, a two-part survey was used. (Such as age, gender -the amount of inclination and tendency of the children towards the suggested designs for the uniforms of nurses)Descriptive and inferential statistics (analysis of variance with repeated measurement, chi-square and Cochran’s test) were used to analysis the data by SPSS software (version 11.5). The table shows that the least tendency amongst girls was for the color navy (20.8) and boys (25.2) showed the least tendency towards patterned uniforms. With regards to the results of the presented study, incorporation of colors such as pink and blue can be recommended for nursing personnel.